Respuesta :

The laplace transform of f(t) is

F (s) =  2/s³ - 2e^{-2s}/s³ + e^{-2s}/s²  + 2e^{-2s}/s  -  3e^{-3s}/s²  + 7e^{-3s}/s

How to express f(t) in unit step function?

Since f(t) = t² 0 < t < 2,

= t - 1 for 2 < t < 3 and

= 7 for t > 3

Since f(t) has discontinuities at t = 0, t = 2, t = 3, expressing f(t) in terms of unit step, we have

t² = t²u(t) - t²u(t - 2)

t - 1 = (t - 1)u(t - 2) - (t - 1)u(t - 3)

=  (t - 1 + 1 - 1)u(t - 2) - [(t - 1 + 3 - 3)u(t - 3)]

=  (t - 2 + 1)u(t - 2) - [(t - 3 + 2)u(t - 3)]

= (t - 2)u(t - 2) + u(t - 2) - (t - 3)u(t - 3) + 2u(t - 3)

f(t) = 7 = 7u(t - 3)

So, f(t) =  t²u(t) - t²u(t - 2) + (t - 2)u(t - 2) + u(t - 2) - (t - 3)u(t - 3) - 2u(t - 3) +  7u(t - 3)

How to find the laplace transform of f(t)

[tex]L[u(t - c)f(t - c)}] = e^{-cs} F(s)[/tex]

and [tex]L[t^{n}] = \frac{n!}{s^{n + 1} }[/tex]

Taking the laplace transform, we have

L{f(t)} = L{t²u(t)} - L{t²u(t - 2)} + L{(t - 2)u(t - 2)} + L{u(t - 2)} - L{(t - 3)u(t - 3)} - L{2u(t - 3)} +  L{7u(t - 3)}

[tex]F(s) = \frac{2!}{s^{3} } - \frac{e^{-2s} 2!}{s^{3} } + \frac{e^{-2s} 1!}{s^{2} } + \frac{e^{-2s} 1!}{s } - \frac{e^{-3s} 1!}{s^{2} } - \frac{2e^{-3s} 1!}{s^{2} } + \frac{7e^{-3s} 1!}{s} \\= \frac{2!}{s^{3} } - \frac{2e^{-2s}}{s^{3} } + \frac{e^{-2s} }{s^{2} } + \frac{2e^{-2s}}{s} - \frac{e^{-3s}}{s^{2} } - \frac{2e^{-3s}}{s^{2} } + \frac{7e^{-3s}}{s}\\[/tex]

[tex]F (s) = \frac{2}{s^{3} } - \frac{2e^{-2s}}{s^{3} } + \frac{e^{-2s} }{s^{2} } + \frac{2e^{-2s}}{s} - \frac{e^{-3s}}{s^{2} } - \frac{2e^{-3s}}{s^{2} } + \frac{7e^{-3s}}{s}\\[/tex]

So, the laplace transform of f(t) is [tex]F (s) = \frac{2}{s^{3} } - \frac{2e^{-2s}}{s^{3} } + \frac{e^{-2s} }{s^{2} } + \frac{2e^{-2s}}{s} - \frac{3e^{-3s}}{s^{2} } + \frac{7e^{-3s}}{s}\\[/tex]

Learn more about Laplace transform here:

https://brainly.com/question/2272409

#SPJ1